Advances in magnetic and optical resonance. - Warren, Warren S. (Advances in magnetic and optical resonance, 1992)
Advances in Magnetic and Optical Resonance, Volume 17 reviews different developing branches of coherent spectroscopy, focusing on the incoherent radiation pulses in optics and magnetic resonance. This book is divided into two chapters. Chapter 1 summarizes the uses and occasional advantages of incoherent radiation pulses in optics and magnetic resonance. The second chapter reviews theoretical developments in zero-field NMR and ESR spectroscopies. Other topics include the nonlinear incoherent spectroscopy; stochastic nonlinear susceptibilities; nonlinear interferometer for magnetic resonance; a.